Enfrentamiento anestésico de paciente con picnodisostosis: a propósito de un caso - Gassmann P., Javiera; Russu C., Daniela (Revista Hospital Clínico Universidad de Chile, 2023)
Pycnodysostosis is a rare autosomal recessive disease with osteoarticular manifestations of great relevance in anesthetic practice. People with this disease are more prone to fractures and craniofacial anomalies that anticipate a difficult-to-manage airway. We present the case of a 19-year-old woman with pycnodysostosis who underwent a reductive mammoplasty under general anesthesia.